Treatment of gastroparesis with botulinum toxin in patient after allogenic bone marrow transplantation - G.M. GALSTYAN; M.V. PASHKOVA; O.Y. POPOVA; P.M. MAKAROVA; D.S. DUBNYAK; L.A. KUZMINA; E.N. PAROVICHNIKOVA (Терапевтический архив, 2018)
The case report of botulinum toxin treatment of gastroparesis in a patient following allogenic bone marrow transplantation is described. The causes of gastroparesis and methods of prevention and treatment are discussed. It was noted that pyloric injection of botulinum toxin can improve symptoms and gastric emptying.